2018
DOI: 10.1039/c7cp05573k
|View full text |Cite
|
Sign up to set email alerts
|

Associative detachment (AD) paths for H and CN in the gas-phase: astrophysical implications

Abstract: The direct dynamical paths leading to Associative Detachment (AD) in the gas-phase, and specifically in the low-temperature regions of the Dark Molecular Clouds (DMC) in the ISM, or in cold trap laboratory experiments, are investigated with quantum chemical methods by using a high-level multi-reference Configuration Interaction (CI) approach that employs single and double excitations plus Davidson perturbative correction [MRSDCI(Q)] and the d-aug-cc-pV5Z basis set. The potential energy curves for H + CN are co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Rotationally inelastic collision processes involving CN À with He atoms and p-H 2 ( j = 0) molecules have been already discussed in our earlier work, 16 where we highlighted that the interaction between H 2 and CN À also leads to Associative Detachment (AD) processes with the destruction of the anionic molecule. 34 This process, however, turns out to be rather slow under cold trap conditions. It thus follows that the use of p-H 2 as a partner in cold traps could also still be an interesting alternative for which one can assess through calculations how feasible would be to use it as a buffer gas at higher temperatures than the more usual He noble gas.…”
Section: Resultsmentioning
confidence: 99%
“…Rotationally inelastic collision processes involving CN À with He atoms and p-H 2 ( j = 0) molecules have been already discussed in our earlier work, 16 where we highlighted that the interaction between H 2 and CN À also leads to Associative Detachment (AD) processes with the destruction of the anionic molecule. 34 This process, however, turns out to be rather slow under cold trap conditions. It thus follows that the use of p-H 2 as a partner in cold traps could also still be an interesting alternative for which one can assess through calculations how feasible would be to use it as a buffer gas at higher temperatures than the more usual He noble gas.…”
Section: Resultsmentioning
confidence: 99%
“…25 Collisional processes of the anion with the astrochemically relevant He and H 2 species 33,34 for rotational transitions have recently been studied and we have also investigated the rotational cooling of this molecular anion with He, Ar, and H 2 as buffer gasses. 35 The CN − anion is also thought to be an important participant as well in reactions in the interstellar medium (ISM) [36][37][38][39] and in the atmosphere of Titan 40 where it has been detected. 41,42 We note in passing that the corresponding neutral species CN was one of the first molecules to be detected in space 43 and cross sections and rates for this species have been investigated and obtained for various rovibrational process in collisions with He and H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, trap losses have been experimentally observed for the Rb + OH − system 23 . We have previously shown that choosing another alkali or alkaline earth atomic species would not lead to detachment 24 since the vertical detachment energy of MOH − depends on M. An other example is the CN − anion for which the AED reaction can occur for some collision partners despite having a large electron affinity (3.862 eV) 25,26 . In conclusion, it is difficult to rely on general molecular properties to predict whether or not to expect AED reactions at low temperatures without explicitly calculating both the anion and neutral PES.…”
Section: Introductionmentioning
confidence: 99%